PENGARUH MOTIVASI KERJA DAN IKLIM KERJA TERHADAP KINERJA GURU DENGAN MODERASIKEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH STUDI PADA SEKOLAH DI YAYASAN INSTITUT INDONESIA 48 CABANG SEMARANG - Hartoyo, Sri Eko (Jurnal Ilmiah Telaah Manajemen, 2017)
The purpose of this study are to find out the effect of work motivation, the atmosphire at school and the transformational leadership of Principal on teacher perfomance of SMP and SMA Institut Indonesia Semarang. The populationof study was teachers of SMP and SMA Institut Indonesia Semarang. The total number of population are 79 teachers. The Primary data were obtained through questionnaire of developed fromvariable indicators. The resulf of Individual parameter test significantly showed motivation, atmosphere of the school, and transformational leadership of principal each have positive effect on teacher performance Morcover. The test results of multiple regression with moderation model, showed that transformational leadership of principals did not moderate the influence of motivation on teacher performance but moderated the influence of atmosphere of the school on teacher performance. Key words : work motivation, atmosphere of the school, the transformational leadership of principal, transformational leadership moderation principal, teacher performance